Bibliometric Analysis of STEM Education Integration in Physical Sciences: Global Trends and Future Directions - El Meraoui, Majd; Makrane, Hanane; Ninis, Ouafae; Khaldi, Mohamed (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Based on a corpus of 127 scientific papers indexed in the Scopus database between 2020 and 2024, this article gives a focused bibliometric analysis on the incorporation of the STEM method in physical science education. The major goal is to present a thorough and organized summary of the scientific development in this area, which is still understudied despite its strategic significance in modern educational systems. Using a strict quantitative approach based on the PRISMA protocol, this study finds the most important publications, the most prestigious journals, the top authors and organizations, and the most popular keywords. According to the data, scientific production has significantly increased since 2023, with contributions from nations like the US, Turkey, and Mexico accounting for a large portion of this growth. The social sciences, engineering, and educational technology make up the majority of the disciplines concerned. This study's unique emphasis on the physical sciences a field that is frequently underrepresented in more general STEM analyses adds value. It improves comprehension of research dynamics, reveals unexplored regions, and suggests strategic directions for future research, teacher preparation, and the creation of evidence-based educational policy by offering an accurate and current mapping of the domain.